The codification of the Hindu personal law in the independent India - Drwal, Anna (Mage.pl, 2016)
Artykuł poświęcony jest kodyfikacji i unifikacji tzw. Hindu personal law w Indiach bo odzyskaniu przez ten kraj niepodległości w 1947 roku. Na przykładzie działań podjętych w Indiach łatwo można zauważyć, że rozwiązania prawne by były efektowne i doprowadzały do zamierzonych celów powinny być dostosowane do warunków społecznych, tradycji oraz zwyczajów danego społeczeństwa.

The article is about the codification of the Hindu personal law in India after this country regained independence in 1947. On the example of the actions taken in India it is easy to noticed that the legal solutions to be effective and to achieve the intended goals have to be adjusted to the social reality, to the traditions and customs of the chosen society.
Keywords: Hindu Code Bil; unification; personal law; India